Software for the study of small communities VKontakte and some of the results - Pechnikov A. A., Ermolaev A. N. (Interactive science, 2018)
authors focused on study of small communities of the social network Vkontakte. For this purpose, specialized program for collecting open data from such communities was developed, which is available in the public domain. The program is easy to use and allows you to collect data about the participants and calculate basic metrics of small communities. The output format is organized in a such way that it can be used without any additional processing in the program for analysis and visualization of networks – Gephi, which significantly enhances the capabilities of researchers. Numerical simulations were made to demonstrate features of the program.
Keywords: программа; социальная сеть; граф; social network; software; ВКонтакте; метрики; ассортативность; предпочтительное присоединение; VKontakte; graph; metrics; assortativity preferential attachment emergence